Challenges Faced by Undergraduate Nursing Students to use of ChatGPT in Classroom Settings in Karachi, Pakistan - Burhanullah; Muhammad Asif; Abdul Razzaqe, (Dialogue Social Science Review (DSSR), 2025)
To explore the challenges faced by undergraduate nursing students in the use of ChatGPT in assignment preparation. This strategy should be applied by teachers in a classroom. To formulate a hypothesis for future research regarding the use of ChatGPT in nursing education services. The strategy of ChatGPT should be limited in classroom settings. Human intelligence should be preferred in the classroom setting to enhance critical thinking. ChatGPT is also a teaching and learning resource. Most of the students are familiar with ChatGPT, and they complete their assignments with the help of ChatGPT. There is the issue regarding a lack of critical thinking among undergraduate nursing students in solving problems. In this generation, most students use ChatGPT to make their assignments quickly, but due to this approach, students do not use their own minds to prepare the assignments. In a classroom setting, whenever the teacher asks questions to check the basic knowledge of students, they do not use their minds, but they are using Chat-GPT. Therefore, they use this approach, but unfortunately, ChatGPT is impacting on human intelligence. According to the authors of most reviewed articles in this paper, ChatGPT and AI strategies in BS-Nursing education is harmful to critical thinking. all institutes of BS-Nursing education should make criteria regarding the limitations of AI strategies in assignments and thesis. Students should be motivated for limited use of ChatGPT and excessive use of brainstorms strategy of human intelligence. Human intelligence is better than ChatGPT (Choi EPH et al., 2023). Research design of this study is qualitative exploratory descriptive study. Sample size was 3 focus groups of Third year undergraduate nursing students in classroom settings. Sampling technique is purposive sampling. Focus group interviews were conducted and each group consists of six students. Audio recorder was used to record the interviews. After the interviews data was translated and transcribed. Data was analyzed according to Braun, and Clark thematic analysis. Rigors of the qualitative study were maintained. A thematic analysis criterion of Braun’s and Clark 2021-2022 was used to analyze the qualitative data. In conclusion the finding of this analysis would provide inside into how undergraduate nursing students are integrating ChatGPT into their learning. In conclusion the finding of this analysis would provide inside into how undergraduate nursing students are integrating ChatGPT into their learning. Majority of students are satisfied and familiar with ChatGPT. And they use the ChatGPT to making take take-home assignments. Some students do not use the ChatGPT in classroom due to lack of access to wifi in the classroom.